Battery resistance reduction and battery materials

JP7609898B2Active Publication Date: 2025-01-07BATTERY ELECTRON TRANSPORT ASSOCIATES INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022576816
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-06-06
Filing Date
2021-06-13
Publication Date
2025-01-07
Estimated Expiration
2041-06-13

Smart Images

  • Figure 0007609898000008
    Figure 0007609898000008
  • Figure 0007609898000009
    Figure 0007609898000009
  • Figure 0007609898000010
    Figure 0007609898000010
Patent Text Reader

Abstract

To provide a battery with reduced resistance. The electrical resistance of the active cathode and anode membranes can be significantly reduced by the addition of small amounts of conductive additives within the battery system. The reduced resistance in the cathode and / or anode results in easier transport of electrons through the battery, increasing power, capacity, and speed while reducing Joule heating losses.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This is an International PCT application entitled RESISTANCE REDUCTION IN BATTERY AND BATTERY MATERIALS, which claims the benefit of U.S. Provisional Application No. 63 / 038,864, filed June 14, 2020, for an invention entitled RESISTANCE REDUCTION IN BATTERY MATERIALS, and U.S. Patent Application No. 17 / 340,063, filed June 6, 2021, for an invention entitled RESISTANCE REDUCTION IN BATTERY AND BATTERY MATERIALS, each of which is incorporated herein by reference. [Background technology]

[0002] 2. Background of the Invention 1. Technical field of the invention The present invention relates to increasing the conductivity of battery cathodes and anodes to improve battery performance, and more particularly to methods and systems for improving battery performance by lowering the electrical resistance both in-plane and especially through-thickness of the active film, thus increasing the conductivity and thereby increasing the charge and discharge rates, ultimately increasing both power and energy densities.

[0003] Various exemplary embodiments of the present invention are described below. Use of the term "exemplary" means exemplary or merely exemplary, and any reference to "the present invention" in this disclosure is not intended to restrict or limit the invention to the exact features or steps of any one or more of the exemplary embodiments disclosed herein. Reference to an "exemplary embodiment," "one embodiment," "embodiment," "several embodiments," "various embodiments," and the like can indicate that one or more embodiments of the present invention so described may include a particular structure, feature, characteristic, or attribute, but not all embodiments necessarily include the particular structure, feature, characteristic, or attribute. Furthermore, repeated use of the phrase "in one embodiment" or "in an exemplary embodiment" may refer to the same embodiment, but does not necessarily do so.

[0004] 2. Related Technologies Among many other technologies, a preferred method for storing electrical energy is the battery. Briefly, a battery is a device in which an anode (negatively charged or reducing electrode) can be filled with electrons by an electrochemical galvanic process, and a cathode (positively charged or oxidizing electrode) undergoes an electrochemical galvanic reaction that reverses and releases the stored electrons into a circuit, thus providing an electric current. Batteries in which these reactions are singular and not reversible are called primary batteries, and they cannot be recharged. Batteries in which these reactions can be reversed multiple times are called secondary batteries or rechargeable. Although the examples described in this disclosure are secondary in nature, those skilled in the art will understand that the concepts described in this disclosure are applicable to both primary and secondary systems.

[0005] The design and material selection of a battery is a function of the galvanic potential between the materials and their ability to provide the designed potential to pass current through a circuit to provide power.

[0006] An important part of the design of a battery is how it collects and distributes current. Although the examples described in this disclosure apply to lithium-ion rechargeable batteries, the concepts disclosed in this disclosure (methods and materials that significantly improve current collection) apply to all batteries, since all batteries generally use current collectors. For the purposes of this disclosure, all battery systems that contain lithium are identified as lithium-ion batteries. The selection of materials used to improve current collection by the methods described in this disclosure must be compatible with the electrochemical galvanic reactions of the battery, so that the selected materials do not become active corrosion products of the battery.

[0007] For purposes of this disclosure, the exemplary embodiments described herein involve lithium ion secondary batteries, specifically lithium iron phosphate or lithium nickel manganese cobalt oxide cathodes and carbon powder anodes, however, one skilled in the art will appreciate that the concepts taught in this disclosure are applicable to any battery in which the materials, methods and techniques described provide the improvements described.

[0008] There are many factors that affect battery performance, including ion transport across separation barriers through both the anode and cathode, chemical reaction kinetics, SEI (solid electrolyte interphase) formation, etc. A key factor is the ability to transport electrons through a system that is many resistors in series; starting from the anode current collector foil, to the anode foil / active material interface, through the anode active material to the electrolyte (where lithium accepts electrons at the anode during charging), transporting that electron and lithium across the barrier to the cathode, separating the electron from the lithium at the cathode, transporting the electron through the cathode active material, then to the active material / foil interface, then moving the electron out of the foil into the device where it functions.

[0009] In the lithium-ion battery systems contemplated by the examples of this disclosure, current collection at the anode is inherently facilitated because the carbon powder used to capture and store lithium ions during the charging cycle is already moderately conductive. Its conductivity is often further improved by the addition of finely divided carbon powder. Nevertheless, the anode film must be thin (e.g., 50-100 microns thick) and applied to a copper or nickel foil current collector. Furthermore, its inherent volume resistivity is such that it limits the rate at which it can be charged, in part, by its ability to pass current through both the active material and the carbon / foil interface and the polymeric binder (another limiting factor is its ability to transport, accept, and store lithium ions). The relationship between voltage, current, and resistance is defined by Ohm's law. If the anode is more conductive, its electrical resistance decreases, and therefore the applied voltage required to pass a given current decreases, or conversely, a higher current flows at a given voltage. This reduction in resistance also results in a reduction in resistive heating losses. Increased conductivity also allows for thicker anode films to be used, thus increasing capacity.

[0010] However, current collection at the cathode is a different story, since many cathode active materials are either non-conductors or poor conductors. In the exemplary embodiments described in this disclosure, lithium iron phosphate (hereinafter LFP) and lithium nickel manganese cobalt oxide (hereinafter NMC) are non-conductive insulators. Typically, however, these materials are combined with a small amount of polymeric binder and conductive sub-micron carbon, then thinly spread onto an aluminum foil substrate. For a given battery design, the cathode film is approximately twice the thickness of the anode film. To provide an appropriate level of conductivity through the thickness of the non-conductive LFP or NMC, a few percent of a moderately conductive finely divided carbon powder (such as that designated Super P) is added to the mixture. To put this into perspective, the volume resistivity of the cathode film is about one to two orders of magnitude less than that of the anode.

[0011] This large difference in conductivity leads to the resistance of the cathode, which is the most prohibitive limiting factor of the discharge rate or capacity of the battery. For example, to obtain a higher discharge rate (power cell), the cathode needs to be made thinner so that the electrons are closer to the current collector foil. However, the thinner the film, the less capacity the battery has. Conversely, the capacity of the battery can be increased by increasing the thickness of the cathode film, but in this case the discharge rate is correspondingly decreased. Thus, one can design for power or design for capacity, but not for both. If the conductivity of the cathode can be significantly improved, a significant increase in capacity or power, or a combination of both, can be achieved.

[0012] The same design philosophy applies to the tradeoff between anode thickness, capacity, and speed. Furthermore, any measure that increases the conductivity of the anode or cathode will lower the resistance or impedance throughout the battery system, increasing the voltage or amperage, and increasing either the rate or capacity, or both. Increasing conductivity also results in reduced Joule heating. Reducing Joule heating is a very important factor for two reasons. First, reduced Joule heating allows this energy to appear in greater capacity. Second, reduced heating results in a cooler and safer battery.

[0013] Despite many recent advances in the battery industry in lithium and its ability to transport, store, and chemically exchange ions and electrons, as well as advances in cathode and anode chemistry, the industry has not seen any significant advances in the electrical conductivity of anode or cathode films for several decades.

[0014] Thus, there is a need for more efficient electrodes, i.e., electrodes that offer significant improvements in efficiency, discharge time, recharge rate, power density, and energy density without sacrificing mass or size. Such electrodes are disclosed in the present disclosure. Summary of the Invention

[0015] Summary of the Invention The present disclosure describes developments that address the current state of the art, and in particular address problems and needs in the art that have not yet been fully resolved by currently available electrodes. The electrodes of the present disclosure are easily implemented and provide significant advances in both power density and energy density. Exemplary electrodes can be used in batteries of all sizes and masses, from use in small electronic devices such as cell phones and laptop computers, to electric vehicles such as golf carts and automobiles, to very large centralized batteries, for example, for renewable energy storage. [Brief description of the drawings]

[0016] BRIEF DESCRIPTION OF THE DRAWINGS Exemplary embodiments of the present invention will be described more fully below with reference to the accompanying drawings, in which several exemplary embodiments of the present invention are shown. Like numbers used in this disclosure refer to like elements throughout. However, the present invention can be embodied in various forms and should not be construed as being limited to the embodiments described in this disclosure; rather, these embodiments are provided so that this disclosure can be put into practice, enabled, and completed. Thus, the disclosed configurations are meant to be merely exemplary and do not limit the scope of the present invention, but should be accorded the full breadth of the appended claims and all equivalents thereof. Moreover, many embodiments, such as adaptations, modifications, variations, and equivalent configurations, are implicitly disclosed by the embodiments described in this disclosure and fall within the scope of the present invention.

[0017] Although certain terms are used in this disclosure, they are used in a generic and descriptive sense only and not for purposes of limitation. Unless otherwise expressly defined in this disclosure, such terms are intended to be given their broad, ordinary and conventional meaning consistent with that applicable in the relevant industry and without being limited to any particular embodiment described below. As used in this disclosure, the article "a" is intended to include one or more elements. When only one element is intended, the term "one", "single", or similar words are used. When used in this disclosure to join lists of elements, the term "or" indicates at least one of the elements but does not exclude multiple elements of the list. In addition, unless otherwise clear from the context of the description, the terms "operator", "user", and "individual" can be used interchangeably in this disclosure.

[0018] The drawings are schematic representations of various components and embodiments and are not drawn to scale. Schematic diagrams are used in this case to aid in understanding the relative relationships between the components. With the understanding that these drawings represent only typical exemplary embodiments of the invention and therefore should not be considered limiting of its scope, the invention will be described and explained with additional specificity and detail with reference to the accompanying drawings, in which: [Figure 1] FIG. 1 is a schematic diagram of an exemplary embodiment of discharging a lithium-ion battery as commonly known in the prior art. [Diagram 2] FIG. 21 is a schematic diagram of an exemplary embodiment of the lithium ion battery of FIG. 1 during recharging as commonly known in the prior art. [Diagram 3] FIG. 3 is a representative depiction of some exemplary embodiments of cathodes commonly known in the prior art, showing the base cathode materials. [Figure 4] FIG. 4 is a representative depiction of a portion of an exemplary embodiment of a reinforced cathode, showing metal coated fibers dispersed throughout the base cathode material of FIG. [Diagram 5] FIG. 5 is a representative depiction of a portion of an alternative enhanced cathode exemplary embodiment showing metal coated fibers and conductive filamentary structures dispersed throughout the base cathode material of FIG. [Figure 6] FIG. 6 is a representative depiction of a portion of an exemplary embodiment of an anode commonly known in the prior art, showing the base anode material. [Figure 7] FIG. 7 is a representative depiction of a portion of an exemplary embodiment of a reinforced anode, showing metal coated fibers dispersed throughout the base anode material of FIG. [Figure 8] FIG. 8 is a representative depiction of a portion of an exemplary embodiment of an alternative enhanced anode, showing metal coated fibers and conductive filamentary structures dispersed throughout the base anode material of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Improving conductivity in both the anode and cathode is desirable and beneficial. The greater benefit comes from the ability to improve the conductivity of the cathode. Anodes are moderately conductive, typically with a volume resistivity of about 0.1 ohm cm; whereas cathodes have a volume resistivity of about 1-10 ohm cm. Due to the low conductivity of the cathode film, the discharge energy capacity of the battery is limited by the inability of the cathode film to conduct electrons through its thickness to the aluminum foil current collector. Conversely, if more power is desired, the film must be made thinner to facilitate faster electron transport to the foil, thus sacrificing capacity. Given a constant thickness, the more conductive the cathode film, the faster the discharge rate. Instead, a film with lower resistivity can be placed thicker at equal resistance, thus increasing capacity at the same power rate. Thus, energy density can be increased by roughly the thickness ratio.

[0020] A significant improvement in the conductivity of either the anode or cathode leads not only to lower resistivity across or through the thickness of the cathode or anode film, respectively, but also to lower resistivity across the entire battery cell in general. As a result, the lower the resistance, the higher the voltage to move a given current, or the higher the current to move at a given voltage. This in turn leads to faster charging and discharging, or the ability to move electrons more easily through thicker films, thus increasing capacity. Joule heating is also reduced, with a corresponding reduction in temperature and energy loss. The reduction in operating temperature also leads to a more efficient and safer battery.

[0021] This disclosure describes various exemplary methods by which the electrical conductivity of the cathode and / or anode can be improved. The magnitude of the improvement can be by a fractional margin (e.g., 25% or 50%) or by an integer margin, such as 2x, 3x, or greater. This disclosure further describes improvements in the operation of the completed lithium-ion cell.

[0022] Additionally, described in this disclosure are exemplary conductive additives for the anode and cathode and their respective effects on the performance of these components. Additionally, battery cells made from these materials are described. Although optimal performance has yet to be achieved, this disclosure clearly demonstrates the effectiveness of these exemplary materials.

[0023] Furthermore, there may be evidence to suggest that morphological changes brought about by the addition of some of these exemplary materials may facilitate ion transport. It is also proposed that the non-carbon surface of highly conductive anode additives may inhibit SEI growth. However, at this time, both of these ideas are hypothetical and not asserted or exemplified in this disclosure.

[0024] Conductive Additives The following exemplary materials were evaluated for increased conductive performance. It should be understood that the present disclosure is not limited to only these exemplary materials and methods. Those skilled in the art, having read the disclosure herein, will understand that the exemplary materials described are illustrative of a broader concept.

[0025] Metal Coated Fiber The addition of metal coated fibers to either the anode or cathode improves the conductivity in both membranes. The metal can be any metal and the fibers can be any fiber, so long as the chemical, physical, and mechanical properties of the fibers and metal coating are compatible with each other and with the respective properties of the selected anode or cathode. Minimizing fiber diameter, maximizing length, optimizing length vs. dispersibility vs. effective concentration, minimizing density, and maximizing fiber conductivity are just a few of the highly interrelated properties to consider.

[0026] Metal coated fibers have been an item of commerce for decades. Many metals (nickel, silver, aluminum, gold, iron, copper, chromium, cobalt, molybdenum, to name a few) have been deposited on a wide variety of fibers (carbon, surface modified carbon, silicon carbide, silicates, borosilicates, alumina, basalt, quartz, aramid, acrylic, rayon, nylon, cotton, silk, to name a few). Smaller fiber diameters are more preferable because they increase the available length and specific surface area of ​​the fiber for a given unit mass, and the conductive surface area per unit mass available for electronic interconnectivity.

[0027] Deposition processes for coating the fibers include reduced pressure processes (PVD, sputtering, evaporation, etc.), wet chemical processes (electroplating, electroless plating), and chemical vapor deposition (CVD). The general conductivity concepts taught in this disclosure are somewhat agnostic to the deposition method, but some of these methods offer better coating uniformity and control.

[0028] Other parameters are important. For example, the choice of fiber (substrate) and the choice of metal (coating) must also be compatible with the chemistry of the battery system. The galvanic corrosion potential of the metal coating for the selected ionic electrolyte must be greater than the operating voltage of the battery, because if it is relatively low, it will galvanically corrode prematurely, as discussed below with respect to Example 1. In addition, the volume resistivity of the coated fiber must be less than that of the active membrane. The wider this improvement, the greater the increase in performance. The length of the fiber is also important. The fibers can be cut to very precise and consistent lengths in the range of 0.1 mm to 1.0 mm. In addition, the fibers can also be precisely cut to conventional lengths of a few mm.

[0029] Dispersion efforts show that precise consistency of fiber length significantly reduces the amount of fiber required for the desired conductivity, thereby reducing viscosity and dispersion issues. However, at concentrations high enough to achieve the desired conductivity, fibers over 1 mm in length may become entangled and may not disperse well. At the other end of the length range, fibers 0.1 mm in length disperse very well, but due to their shorter aspect ratio, larger amounts are required for the desired conductivity. This additional material loading increases mass and cost, but more importantly, it displaces active battery material, thereby correspondingly reducing available capacity.

[0030] The use of 0.5 mm or about 0.5 mm fibers is particularly suitable for dispersion, and the length can be adjusted upwards or downwards from 0.5 mm depending on other factors such as diameter or to facilitate dispersion. Although fibers manufactured by any known means can vary in length within the range of 0.1 mm to 1 mm mentioned above, it is preferable to use precision cut fibers, where precision cut fibers means that the fibers are uniform to ±10% of the selected length (e.g., for 0.5 mm fibers, all fibers are 0.45 to 0.55 mm). At that length, the fibers can be dispersed in the active anode and cathode materials up to about 10% by weight. However, in practice, it is difficult to achieve dispersions of more than 5%, and dispersions of more than about 2% to 3% do not contribute to conductivity commensurate with their additional mass, cost, or replacement of active material.

[0031] Various examples of potential metal coated fiber additives are given below along with a description of their relative effectiveness as additives:

[0032] Carbon Fiber Carbon fibers in continuous woven, felt, or chopped form have been the subject of extensive battery research as current collectors, support members, or mechanical reinforcements, but these fibers do not exhibit sufficient conductivity to achieve the desired objectives of the present disclosure.

[0033] Nickel Coated Carbon Fiber Nickel coated carbon fibers are an item of commerce. Their small diameter, low density, high aspect ratio, high linear mass yield, excellent electrical conductivity, and environmental stability all combine to provide an excellent conductive network at very low volumes. However, since nickel corrosion to lithium occurs at 3.75 volts and lithium NMC cathodes operate at 4.2 volts, the nickel on the fiber corrodes at 3.75 volts and therefore the battery produced will not cycle and will fail at 3.75 volts. However, in lithium iron phosphate (LFP) batteries, the maximum voltage is 3.6V and the operating voltage is around 3.2V. Thus (as shown in the example), nickel coated fibers work well. For NMC systems, a metal that can withstand more than 3.75V to lithium is required for operation up to 4.2V. Fortunately, aluminum to lithium reacts at 4.7V. Thus, in the example, aluminum coated fibers are shown to do this LFP system. The lesson here is that the potential voltage of the conductive metal compared to the electrolyte ions must be higher than the operating voltage of the element, whether it is a cathode or an anode. Thus, nickel-coated fibers are predicted to work well in lithium-ion anodes, but not in lithium-ion cathodes. Such cases are illustrated in some examples below. If the operating voltage of the cathode is low enough, the use of nickel materials described in this disclosure is an effective route to reduced resistivity.

[0034] Aluminum Coated Fiber The use of aluminum coated fibers in lithium ion batteries is a good choice because the lithium / aluminum reaction occurs at 4.7 volts and does not lead to corrosion reactions until 4.7 volts. The use of lithium NMC cathodes operating at 4.2 volts does not lead to corrosion reactions. As evidence, current collectors in lithium ion batteries are made of aluminum foil.

[0035] Many types of aluminum coated fibers can be contemplated. Aluminum is coated onto fibers and fabrics, usually through a vacuum or melt process. The applications of these products are usually optical in nature, such as reflectors (fiber optic or mylar balloons) or heat reflectors (globes for high temperature processes). They have been items of commerce for decades. However, these fibers are large in diameter (usually greater than 25 microns) and have a density of about 2.7 g / cc. Although they may be viable candidates, their large diameter and moderate density result in less than desirable linear yields.

[0036] Aluminum Coated Carbon Fiber Aluminum coated carbon fiber is not a viable option as aluminum carbides form easily.

[0037] Aluminum coating over nickel coating over carbon fiber If a barrier such as a nickel film or coating is placed between the carbon and the aluminum, the aluminum can be deposited as a thin film on the nickel. This is shown in the successful example below. However, after about a week of cycling, the nickel begins to react with the lithium and the battery fails.

[0038] Aluminum coatings on other textiles Any fiber that does not form carbides during or after deposition, or at least its surface is already carbide, is a candidate for aluminum deposition. The aluminum deposition is deposited by chemical vapor deposition from any aluminum-containing organometallic compound. Examples of aluminum-coated fibers that have been demonstrated include fibers of silicon carbide, silicate, alumina, aluminum borosilicate, basalt, quartz, aramid, etc. Each of these fibers has been demonstrated to readily accept thin aluminum films, but this list is by no means exhaustive. Thus, the fiber (substrate) of the aluminum-coated fiber can be selected from the group including carbon, pan ox (PAN oxide), silica, quartz, silicate, alumina, aluminosilicate, borosilicate, glass, mineral, carbide, nitride, boride, polymer, cellulose, inorganic fibers, and organic fibers.

[0039] Surface modification of carbon fibers The surface of the carbon fiber can be modified to silicon carbide, and then aluminum is easily coated onto the silicon carbide surface. This fiber offers the smallest diameter and lowest density approach.

[0040] Other metal coated fibers Such metal coated fibers have proven useful, such as copper coated carbon fibers.

[0041] Branched metals in powder and filament form When nickel is actively used for its conductivity, such as in lithium ion anodes or LFP cathodes, certain nickel powders may function to provide additional electrical paths between metal-coated fibers or to provide multiple conductive paths through the active material / polymer / foil current collector interface. The synergistic effect of adding other conductive solid shapes, such as platelets or spheres, is known to increase the interconnectivity between metal-coated fibers. One particularly advantageous method uses nickel powders with highly filamentary and branched structures (e.g., Inco type 255 powder) in which the main branches of the structure are generally greater than 1 micron in diameter and somewhat branched. Filamentary branched metals, known as "nanostrands," typically have branches less than 1 micron in diameter and exhibit very extensive branching ("nanostrands" are available from Conductive Composites Company, Heber City, Utah).

[0042] By using a combination of additives such as metal-coated fibers and filamentary branched structures such as branched nickel powder or nanostrands, the metal-coated fibers and the high aspect ratio conductive filamentary structures work together to build a comprehensive network of electron transport pathways. The physical properties of the metal-coated fibers and one or more high aspect ratio conductive filamentary structures facilitate the construction of an interfiber electron transport network that transfers electrons between the anode and current collector interfaces. The metal-coated fibers act like logs, which are elongated linear electron transport conduits, and the conductive filamentary structures act like tumbleweeds that electrically interconnect the logs.

[0043] When such a combination of additives is used in the anode, the conductivity of the anode is further improved. Although the carbon powder of the anode is already somewhat conductive, the spaces between the filamentary networks of the conductive filamentary branched structures are of approximately the same size and shape as the particle size of the carbon powder. Thus, the filamentary branched structures wrap the carbon particles with themselves in a somewhat three-dimensional manner, like a spider web or net (hereinafter referred to as "nanonet"). This "nanonet" phenomenon leads to a much higher level of electrical interconnectivity between the carbon particles, the filamentary branched structures, the metal-coated fibers, and the current collector foil. This effect is more pronounced for the nanostrands due to their smaller diameter and greater degree of branching.

[0044] As will be shown in the examples provided in the detailed description below, the amount of metal coating on the fibers is an important parameter in modifying the conductivity.

[0045] These and other features of the exemplary embodiments of the invention will become more fully apparent from the drawings, examples, and description that follow, or may be learned by the practice of the invention as set forth hereinafter.

[0046] Detailed Description of the Invention Exemplary embodiments of the present disclosure are best understood by reference to the drawings, in which like parts are designated with like numerals throughout. It will be readily understood that the components of the exemplary embodiments of the present invention, as generally described and illustrated in the drawings and examples of the present disclosure, can be arranged and designed in a wide variety of different configurations. Thus, the following more detailed description of the exemplary embodiments, as illustrated in the drawings and examples, is not intended to limit the scope of the present invention as claimed, but merely represents exemplary embodiments of the disclosure.

[0047] This detailed description, with reference to the drawings, describes a representative rechargeable lithium-ion battery 10 known in the prior art, which operates with a standard cathode 12 made of a base cathode material 14, and a standard anode 16 made of a base anode material 18. Exemplary embodiments of the invention include modified electrodes having increased conductivity that may be components of an enhanced battery, either separately or together.

[0048] With reference to Figure 1, a representative rechargeable lithium-ion battery 10 known in the prior art is generally depicted. The lithium-ion battery 10 includes a standard cathode 12 made of a base cathode material 14, a standard anode 16 made of a base anode material 18, an electrolyte 20, a separation barrier 22, an anode current collector foil 24, and a cathode current collector foil 26, contained within a battery housing 28. The base cathode material 14 can be any of a number of cathode compounds known to be used in batteries; however, for purposes of this description, the battery 10 is a lithium-ion battery 10, and exemplary base cathode materials 14 can include lithium iron phosphate (LFP) and lithium nickel manganese cobalt oxide (NMC), as well as any other cathode materials used in lithium-ion batteries. The base anode material 14 can be any of the anode materials known to be used in batteries; however, for purposes of this description, the battery 10 is a lithium-ion battery 10, and exemplary base anode materials 14 can include carbon powder, graphite powder, and any other cathode materials used in lithium-ion batteries. Such compounds further contain small amounts of polymers used as binders. Additionally, the electrolyte 20 most often used in lithium-ion batteries 10 is an organic solution of a lithium salt, such as LiPF6. The important role of the electrolyte 20 is to transport positive lithium ions between the cathode 12 and the anode 16.

[0049] The battery 10 operates to transport electrons through a system of components. In FIG. 1, in a discharge mode, electron transport begins at the anode current collector foil 24, then through the anode foil / active material interface to the anode active material (in this case, the standard anode 16). The discharge direction of electron flow (indicated by the schematic flow path 30) is generally indicated by the negative-to-positive arrow A. Positively charged lithium ions 32 move through the electrolyte 20 (in this case, lithium accepts electrons at the standard anode 16 during charging), and the electrons (of the lithium ions 32) and lithium pass through the separation barrier 22 (as indicated by the dashed arrow B) to the standard cathode 12. Separation of the electrons from the lithium (of the lithium ions 32) occurs at the standard cathode 12. The electrons are transported through the cathode active material (standard cathode 12) to the active material / foil interface, and then transfer the electrons out of the cathode current collector foil 26 to the device in which they function.

[0050] Figure 2 shows the battery 10 of Figure 1 during charging. The charging direction of electron flow (indicated by schematic flow path 30) reverses as shown diagrammatically by positive-to-negative arrow C. Positively charged lithium ions 32 migrate within electrolyte 20 from standard cathode 12 across separation barrier 22 (as indicated by dashed arrow D) to standard anode 14.

[0051] Significant improvements in the conductivity of either the anode or cathode, or both, result in lower resistivity across or through the thickness of the respective cathode or anode films, as well as generally throughout the entire battery cell. As a result, the lower the resistance, the higher the voltage that will move a given current, or the higher the current that will move at a given voltage. This in turn results in faster charging and discharging, or the ability to move electrons more easily through thicker films, thus increasing capacity. Joule heating is also reduced, with a corresponding reduction in temperature and energy loss. The reduction in operating temperature also translates into a more efficient and safer battery.

[0052] Exemplary conductive additives 34 for the anode 16 and cathode 12 (see FIGS. 4, 5, 7, and 8) are described in this disclosure that significantly improve the conductivity and enhance the performance of these components 12, 16, and the battery 10 in which they are used. By dispersing some of these exemplary additives 34 within the base cathode material 14 and / or base anode material 18, the resulting enhanced cathode 36 and / or enhanced anode 44 exhibit increased conductivity and ion transport within the battery system is facilitated. It is also proposed that the non-carbon surface of the highly conductive anode additives may inhibit SEI growth.

[0053] 3 is a representative depiction of some of the illustrative embodiments of cathode 12 commonly known in the prior art and shows the base cathode material 14 from which cathode 12 is made. As noted above, base cathode material 14 can be any of the many cathode compounds known for use in batteries.

[0054] An exemplary embodiment of a reinforced cathode 36 showing metal coated fibers 38 dispersed throughout the base cathode material 14 is depicted in Figure 4. The depiction in Figure 4 is not drawn to scale, nor does it indicate any particular quantity levels. Rather, the depiction is merely intended to provide context to the dispersion of the metal coated fibers 38 within the base cathode material 14.

[0055] FIG. 5 is an enlarged view compared to FIG. 4 and depicts an alternative exemplary embodiment of the reinforced cathode 36, showing metal coated fibers 38 and high aspect ratio conductors 40, e.g., conductive filamentary structures 42, dispersed throughout the base cathode material 14. Such high aspect ratio conductors 40 are smaller than the metal coated fibers 38 in at least one material physical aspect, such as diameter, mass, or volume, and may also exhibit branching. Electrical conductivity between the conductive metal coated fibers 38 is further improved by the addition of such high aspect ratio conductors 40. Again, the depiction of FIG. 5 is not drawn to scale, nor does it represent any specific quantity levels. Rather, the depiction is merely intended to provide context to the dispersion of the metal coated fibers 38 within the base cathode material 14.

[0056] 6 is a representative depiction of some of the illustrative embodiments of anodes 16 commonly known in the prior art, showing the base anode material 18 from which the anode 16 is made. As noted above, the base anode material 16 can be any of the anode materials known for use in batteries.

[0057] An exemplary embodiment of a reinforced anode 44 showing metal coated fibers 38 dispersed throughout the base anode material 18 is depicted in Figure 7. The depiction in Figure 7 is not drawn to scale, nor does it indicate any particular quantity levels. Rather, the depiction is merely intended to provide context for the dispersion of the metal coated fibers 38 within the base anode material 18.

[0058] Figure 8, an enlarged view compared to Figure 4, depicts an exemplary embodiment of an alternative reinforced anode 44, showing metal coated fibers 38 and high aspect ratio conductors 40, e.g., conductive filamentary structures 42, dispersed throughout the base anode material 18. Such high aspect ratio conductors 40 are smaller than the metal coated fibers 38 in at least one material physical aspect, such as diameter, mass, or volume, and may also exhibit branching. Electrical conductivity between the conductive metal coated fibers 38 is further improved by the addition of such high aspect ratio conductors 40. EXAMPLES

[0059] example Below are some representative examples that demonstrate the concepts and advancements disclosed in this disclosure:

[0060] Fiber Selection (Examples 1-3)

[0061] Example #1 – Nickel Coated Carbon Fiber in Cathode Nickel-coated carbon fibers (7 micron diameter, 40% nickel coating, i.e., 0.25 micron thick, precision cut to 0.50 mm) provided excellent conductivity for the cathode. The addition of 2% by weight of the described fibers lowered the through-thickness resistance of a 100 micron membrane from 3.5 ohms (no fibers) to 1.5 ohms (2% fibers). However, lithium-ion coin cells made from these membranes would not cycle. The cells were found to corrode at 3.75 volts before reaching the operating condition of 4.2 volts. This is because the half-cell potential of nickel and lithium is 3.75 volts. However, this demonstrated that conductivity could be significantly improved, suggesting that nickel-coated fibers should work in systems that remain below about 3.5 volts (see anode example below).

[0062] Example #2 – Aluminum Coated Fiber The half-cell potential of aluminum and lithium is 4.7 volts. Therefore, the aluminum coated fiber should be able to withstand a cathode with a lithium operating voltage of 4.2 volts. In this case, a 0.2 micron coating of aluminum was plated on top of a 0.1 micron coating of nickel on the carbon fiber. The dual coated fiber was cut to a length of 0.50 mm. When this fiber was added to the cathode at 2% by weight, the cell could be cycled successfully for about a week, after which the underlying nickel entered the reaction. When these cathode membranes were made, the standard cathode (made with the base cathode material) was 90 microns thick, and the fiber-filled cathode (base cathode material filled with metal-coated fiber) was 110 microns thick. This is likely because the added fiber added support and drag, pulling the slightly thicker membrane. The table below compares the thickness, resistance, voltage, and capacity of these two cells. (Each value is the average of three samples.)

[0063] [Table 1]

[0064] Note that the fiber-filled membrane is 23% thicker than the standard membrane, yet exhibits the same resistance and voltage as the thinner original membrane. Thus, the capacity of the fiber-filled membrane is increased by 23%, which means higher capacity at the same speed (driving resistance) or higher speed at equal capacity.

[0065] Example #3 – Process for coating fibers with CVD aluminum All of the aforementioned fibers were coated with an aluminum CVD (chemical vapor deposition) process, precision cut to 0.5 mm, and added to the cathode. Examples of fibers include (but are not limited to) silicon carbide, borosilicate, quartz, mineral (basalt), surface modified carbon, and organic (aramid-Kevlar). In each of these cases, the addition of 1% to 4% of precision cut aluminum-CVD coated fibers improved the conductivity of the coating by values ​​similar to those of Example #1 above. Each of these fibers adds certain advantages or disadvantages unique to that particular fiber, but they all work to improve the conductivity of the cathode.

[0066] Cathode (Example 4)

[0067] Example #4 - Aluminum coated fiber precision cut to 0.5mm These coated fibers were dispersed in a standard cathode mix at 3% by weight (always setting aside a portion of the mix for a control), which was repeated multiple times with the largest variable being batch-to-batch or fiber type variation in the conductivity of the aluminum coated fibers.

[0068] Films were extruded onto aluminum foil using a doctor blade, adjusting the height of the blade depending on the desired thickness and the solvent to solids ratio of the mixture to achieve consistent film thickness and mass. After drying, the uncalendared films were tested for volume resistivity according to ASTM method D2739. The following table reports some of these comparative batches.

[0069] [Table 2]

[0070] Using sample set D, the samples were calendered and measured for composite volume resistivity (CVR) and interfacial resistivity (IR).

[0071] [Table 3]

[0072] Example #5 – Higher fiber content in cathode A standard cathode mix was loaded with 3%, 4%, 5%, and 6% nickel coated fibers with a 40% nickel coating (250 nm thick) precision cut to 0.5 mm. Attempts to mix more than 6% resulted in poor dispersion. However, the table below shows the improvement in through thickness volume resistivity when films of equal thickness were drawn from these mixes.

[0073] The volume resistivity of the cathode membrane was modified with 40% nickel and 0.5 mm long precision cut nickel coated carbon fibers.

[0074] [Table 4]

[0075] Example #6 - Effect of Nickel Coating Percentage on Fiber In the same test as Example #5, one sample was made with 75% nickel coating on the fiber, and the mass and thickness of the nickel on the fiber (carbon fiber) was 4 times (the basis mass is 0.76 gm / meter, while 40% is 1.28 gm / meter, and 75% is 3.00 gm / meter). The density of the 40% nickel coated fiber is 2.6 gm / cc, while the density of the 75% nickel coated fiber is 5.5 gm / cc. For this example, the objective was to add a volume that was consistent with that representative of the loading of the 40% nickel coated fiber. The loading mass range for the 75% nickel coated fiber can be up to 15%, but for this example, 10% by mass was chosen. This corresponds to a fiber volume of 4.8% of the 40% nickel coated fiber. At this amount, the dispersion was good and the film pulled well. However, the through-thickness volume resistivity of this film was outstanding at 0.40 ohm cm, nearly double that of the best of the 40% nickel-coated fibers. This higher conductivity and nickel loading not only results in greatly improved performance, but also improves the current carrying capacity, making it more suitable for power cells.

[0076] Anodes (Examples 7, 8 and 9)

[0077] Example #7 – Anode containing copper coated carbon fiber Since the anode current collector is copper foil, copper may be a viable candidate for anode improvement. In this example, up to 8% copper-coated carbon fiber was added to the anode. The copper coating on the AS4 fiber is 40% by weight. The copper-coated carbon fiber was obtained from Technical Fiber Products, Schenectady, NY, and precision cut to 0.50 mm length. The resistivity of the resulting anode was reduced from 253 ohms to 112 ohms, i.e., a 220% improvement in conductivity. As a result, the voltage of the anode was reduced from 1.0 ohms to 0.8 ohms. This lower voltage means a higher capacity at a given charge rate, or alternatively a higher charge rate.

[0078] Example #8 - Anode containing precision cut nickel coated carbon fiber (NiPCF) Nickel is also a viable element to include in the anode. Precision cut nickel coated carbon fiber was obtained from The Conductive Group, Heber City, Utah. The nickel coating on the AS4 carbon fiber was 40% by weight, i.e., 0.25 microns thick. Recalling that the anode is already composed of conductive graphite powder, the addition of 5% or 10% by weight of NiPCF alone did not significantly improve the conductivity (CVR or IR) of the anode film. Some samples did not show a statistically significant improvement, while others showed an improvement of perhaps about 25%. These improvements are believed to be marginal.

[0079] Example #9 - Anodes containing filamentary branched structures Nickel powders produced by chemical vapor decomposition may be produced in two distinct geometric classes; spherical (Type 1 powder), or filamentary (Type 2 powder). Type 1 powders do little to increase conductivity until the quantities are exceptionally high, since the particles must be in intimate contact with one another. However, filamentary powders become conductive at smaller quantities due to the higher aspect ratio, and in part because filamentary powders usually exhibit some degree of branching. Larger diameter forms of these powders (usually greater than 1 micron in diameter of the main branch) are available through Vale or Novamet, particularly as Chip 255 powder (and its derivatives). Nanostrands are filamentary branched metals with smaller diameters that contain more extensive branching. Nanostrands are available from The Conductive Group, Heber City, Utah.

[0080] The Type 255 powder alone did not significantly increase the conductivity of the system, but the nanostrands showed a significant increase in the conductivity of the anode mix.

[0081] Of interest is the combination of NiPCF fibres with filamentary branched structures, which form the so-called "log and tumbleweed" network.

[0082] The following table compares the CVR and IR of standard anode membranes versus 5% NiPCF, 5% Type 255, 5% Nanostrand, and 5%+5% NiPCF / 255, and 5%+5% NiPCF / Nanostrand:

[0083] [Table 5]

[0084] It is noted that the CVR of individual additives does not seem to be very effective, but combinations do change the CVR somewhat. They all have some effect on the IR, some quite significant. This is likely because none of the individual additives are as conductive as carbon powder. However, the "logs and tumbleweeds" provide an opportunity for more complex electron transport. The IR, or interfacial resistance, suggests that additive combinations take multiple paths directly across the ever-present polymer binder barrier into the underlying foil. Calendering appears to provide additional physical pressing of the conductor into the foil.

[0085] It has been observed that the filamentous branched structures (tumbleweeds) not only provide multiple high aspect ratio paths to the nickel coated fibers (logs), but they also tend to overlie or contact the carbon particles in multiple locations (each such contact is hereafter referred to as a "contact point"). With more open and branched nanostrands, they tend to wrap and encase the carbon particles with themselves, like a spider web or net, creating a nanonet, exhibiting multiple contact points. It is this multiple contact and nanonetting pattern that adds more opportunities for conduction. It becomes a model of "logs, tumbleweeds and nanonets" and is unique in its ability to collect current at higher velocities, higher amperages, and lower voltages.

[0086] The NiPCF / nanostrand sample was selected as the anode and used to fabricate an experimental pouch cell battery along with the cathode described near the end of Example 4.

[0087] Pouch cell battery (Examples 10 and 11)

[0088] Example #10 - Modified anode with standard cathode A control pouch cell was made with a standard cathode and a standard anode. A second pouch cell was constructed with a standard cathode and an anode modified with nickel coated fibers. The standard anode had CVR and IR values ​​of 0.12 and 0.10 ohms, respectively. The modified anode had CVR and IR of 0.065 and 0.0081, respectively. Thus, the CVR and IR of the modified anode were improved by 1.9x and 12.3x, respectively. The capacity at various discharge rates as a result of the improved conductivity is shown in the following table:

[0089] [Table 6]

[0090] This is believed to be due to the conductive network of the logs, tumbleweeds and nanonets mentioned above, which allows such structures to collect and transport electrons more efficiently. It was also observed that the logs and tumbleweeds create a more open structure, thus creating easier and more numerous pathways for lithium ion transport.

[0091] Example #11 - Modified cathode with standard anode For this example, pouch cells were constructed with a standard anode and a lithium iron phosphate cathode. While the control cell used a standard lithium iron phosphate cathode, the second cell used a cathode containing 3% (by weight) of 40% nickel coated carbon fiber precision cut to 0.5 mm, as given in the results of Example #5. This is a fairly conservative amount.

[0092] The table below shows the discharge voltage and capacity of these cells at various discharge rates. [Table 7]

[0093] This data shows that the addition of a moderate amount of conductive fiber to the cathode simultaneously lowers the resistance and impedance, allowing for higher voltages or currents, or both.

[0094] For exemplary methods or processes of the invention, the order and / or arrangement of steps described in this disclosure is exemplary and not limiting. Thus, although various process or method steps may be shown and described as being in an order or temporal arrangement, any such process or method steps are not limited to being performed in any particular order or arrangement unless otherwise indicated. In fact, such process or method steps can typically be performed in different orders and arrangements and still fall within the scope of the invention.

[0095] Additionally, any reference to advantages, benefits, unexpected results, preferred materials, or enablement of the invention is not intended as an acknowledgement that the invention has been preliminarily reduced to practice or that any testing has been performed.Similarly, unless otherwise stated, use of a verb in the past tense (present perfect or past tense) is not intended to indicate or suggest that the invention has been preliminarily reduced to practice or that any testing has been performed.

[0096] Exemplary embodiments of the present invention are described above. Any element, operation, or provision used in this description should not be construed as important, necessary, critical, or essential to the present invention unless expressly described as such. Although only a few exemplary embodiments are described in detail in this disclosure, those skilled in the art will readily recognize that many modifications are possible in these exemplary embodiments without substantially departing from the novel teachings and advantages of the present invention. Therefore, all such modifications are intended to be included within the scope of the present invention as defined in the appended claims.

[0097] In the claims, any means-plus-function clause is intended to cover the structures described in this disclosure as performing the recited function, and to cover equivalent structures as well as structural equivalents. Thus, nails and screws may be equivalent structures, even though they may not be structural equivalents in that nails use cylindrical surfaces to fasten wooden parts and screws use helical surfaces in the context of fastening wooden parts. No construction under § 112 is intended unless the very phrase "means for" (performing a particular function or step) appears in the claims. In addition, it is not intended that the scope of patent protection afforded to the invention be defined by reading into any claims limitations found in the disclosure that do not expressly appear in the claims themselves.

[0098] Although specific embodiments and applications of the present invention have been described, it should be understood that the present invention is not limited to the precise configuration and components disclosed in this disclosure. Various modifications, changes and variations apparent to those skilled in the art can be made in the configuration, operation and details of the methods and systems of the present invention disclosed in this disclosure without departing from the spirit and scope of the invention.

[0099] Those skilled in the art will appreciate that the present embodiments may be embodied in other specific forms without departing from the structure, method, or other essential features broadly described in this disclosure and set forth in the following claims. The described embodiments are to be considered in all respects as merely illustrative and not restrictive. The scope of the present invention is therefore indicated by the appended claims rather than by the foregoing description. All changes that come within the meaning and range of equivalency of the claims are intended to be embraced within their scope. The present disclosure also includes the following: Aspect 1 1. A battery cathode having enhanced electrical conductivity for use in a battery having an electrolyte having an electromotive potential, said battery cathode comprising: A base cathode material having an operating voltage; and at least one additive dispersed within the base cathode material to form a dispersed mixture; The at least one additive is a plurality of metal coated fibers having diameters between 3 microns and 20 microns, a thickness of the metal coating between 0.1 microns and 3 microns; a fiber length between 0.1 mm and 1.0 mm, the metal coated fibers comprising a metal having an electromotive potential, the selection of a metal for the metal coating and a thickness of the metal coating affecting electrical conductivity and electromotive reactivity; a fiber diameter and fiber length of the metal coated fibers affect an aspect ratio, a surface area, and a dispersibility of the metal coated fibers within the base cathode material, the dispersive mixture imparting improved electrical and mechanical properties to the battery cathode; A battery cathode, wherein the operating voltage of the base cathode material remains lower than the reaction voltage of the metal with respect to the electrolyte such that the metal may corrode with the electrolyte at a reaction voltage. Aspect 2 2. The battery cathode of claim 1, wherein electrical conductivity between the conductive fibers is further enhanced by the addition of high aspect ratio conductors that are smaller than the metal coated fibers. Aspect 3 3. The battery cathode of claim 2, wherein the high aspect ratio conductor has a branched structure. Aspect 4 the electrolyte is lithium-containing; 2. The battery cathode of claim 1, wherein the metal coated fibers comprise aluminum coated fibers when the operating voltage of the base cathode material is greater than 3.76 volts. Aspect 5 the electrolyte is lithium-containing; 2. The battery cathode of claim 1, wherein the metal coated fibers comprise nickel coated fibers when the operating voltage of the base cathode material is less than 3.76 volts. Aspect 6 2. The battery cathode of claim 1, wherein the fibers are selected from the group of materials consisting of carbon, pan ox, silica, quartz, silicates, alumina, aluminosilicates, borosilicates, glass, minerals, carbides, nitrides, borides, polymers, cellulose, inorganic fibers, and organic fibers. Aspect 7 2. The battery cathode of claim 1, wherein the metal coated fiber is precision cut to a desired length such that the metal coated fiber is within ±10% of the desired length. Aspect 8 2. The battery cathode of claim 1, wherein the fibers have a carbide surface, the carbide surface being chemically acceptable for aluminum deposition, and the aluminum deposition being deposited from any aluminum-containing organometallic compound. Aspect 9 2. The battery cathode of claim 1, wherein the metal coated fibers are dispersed in the base cathode material in a loading range of up to 15% by weight, such that the battery cathode exhibits reduced volume resistivity and interfacial resistivity relative to an unfilled base cathode material. Aspect 10 2. The battery cathode of claim 1, wherein the improved electrical and mechanical properties of the dispersion mixture relative to the base cathode material include improved electrical conductivity of the battery cathode and at least one of the following improvements: lower resistance, lower impedance, increased voltage capacity, increased amperage capacity, increased speed and power, lower Joule heating, lower and safer operating temperature, and commensurate higher capacity. Aspect 11 A battery anode having enhanced electrical conductivity for use in a battery having an anode electrolyte having an electromotive potential, said battery anode comprising: A base anode material having an operating voltage; and At least one anode additive dispersed within the base anode material to form an anode dispersion mixture. Including, The at least one anode additive is a plurality of metal coated fibers having diameters between 3 microns and 20 microns, the metal coating having a thickness between 0.1 microns and 3 microns; a fiber length between 0.1 mm and 1.0 mm, the metal coated fibers comprising a metal having an electromotive potential, the selection of a metal and thickness for the metal coating affecting electrical conductivity and electromotive reactivity; the fiber diameter and fiber length of the metal coated fibers affect the aspect ratio, surface area, and dispersion of the metal coated fibers within the base anode material, the anode dispersion mixture of metal coated fibers thus characterized in the base anode material imparting improved electrical and mechanical properties to the battery anode; A battery anode, wherein the operating voltage of the base anode material remains lower than the reaction voltage of the metal with respect to the anode electrolyte such that the metal may corrode with the anode electrolyte at a reaction voltage. Aspect 12 12. The battery anode of claim 11, wherein electrical conductivity between the conductive fibers is further enhanced by the addition of high aspect ratio conductors that are smaller than the metal coated fibers. Aspect 13 12. The battery anode of claim 11, wherein the base anode material comprises carbon powder of finely divided carbon powder particles. Aspect 14 12. The battery anode of claim 11, wherein the metal coating of the metal coated fibers is selected from the group of metals consisting of nickel, copper, and aluminum. Aspect 15 12. The battery anode of claim 11, wherein the fibers are selected from the group of materials consisting of carbon, pan ox, silica, quartz, silicates, aluminas, aluminosilicates, borosilicates, glasses, minerals, carbides, nitrides, borides, polymers, cellulose, inorganic fibers, and organic fibers. Aspect 16 12. The battery anode of claim 11, wherein the plurality of metal coated fibers are dispersed in the base anode material in a maximum loading range of 15% by weight. Aspect 17 12. The battery anode of claim 11, wherein the improved electrical and mechanical properties of the anode dispersion mixture relative to the base anode material comprise improved electrical conductivity of the battery anode and at least one of the following improvements: lower resistance, lower impedance, increased voltage capacity, increased amperage capacity, increased speed and power, lower Joule heating, lower and safer operating temperature, and commensurate higher capacity. Aspect 18 A battery having enhanced electrical conductivity having an electrolyte having an electromotive potential, the battery comprising a battery cathode and a battery anode; The battery cathode comprises: A base cathode material having an operating voltage; At least one additive dispersed within the base cathode material to form a dispersed mixture. Including, The at least one additive is a plurality of metal coated fibers having diameters between 3 microns and 20 microns, a thickness of the metal coating between 0.1 microns and 3 microns; a fiber length between 0.1 mm and 1.0 mm, the metal coated fibers comprising a metal having an electromotive potential, the selection of a metal for the metal coating and a thickness of the metal coating affecting electrical conductivity and electromotive reactivity; a fiber diameter and fiber length of the metal coated fibers affect an aspect ratio, a surface area, and a dispersibility of the metal coated fibers within the base cathode material, the dispersive mixture imparting improved electrical and mechanical properties to the battery cathode; the operating voltage of the base cathode material remains lower than the reaction voltage of the metal with respect to the electrolyte, since the metal may corrode with the electrolyte at a reaction voltage; The battery anode comprises: A base anode material having an operating voltage; and At least one anode additive dispersed within the base anode material to form an anode dispersion mixture. Including, The at least one anode additive is a plurality of metal coated fibers having diameters between 3 microns and 20 microns, the metal coating having a thickness between 0.1 microns and 3 microns; a fiber length between 0.1 mm and 1.0 mm, the metal coated fibers comprising a metal having an electromotive potential, the selection of a metal and thickness for the metal coating affecting electrical conductivity and electromotive reactivity; the fiber diameter and fiber length of the metal coated fibers affect the aspect ratio, surface area, and dispersion of the metal coated fibers within the base anode material, the anode dispersion mixture of metal coated fibers thus characterized in the base anode material imparting improved electrical and mechanical properties to the battery anode; The battery, wherein the operating voltage of the base anode material remains lower than the reaction voltage of the metal with respect to the anode electrolyte such that the metal may corrode with the anode electrolyte at a reaction voltage. Aspect 19 20. The battery of claim 18, wherein electrical conductivity in the battery cathode between the conductive metal coated fibers is further improved by the addition of high aspect ratio conductors that are smaller than the metal coated fibers. Aspect 20 20. The battery of claim 18, wherein electrical conductivity in the battery anode between the conductive metal coated fibers is further improved by the addition of high aspect ratio conductors that are smaller than the metal coated fibers. [Explanation of symbols]

[0100] Reference number Lithium-ion battery or battery 10 Standard Cathode or Cathode 12 Base cathode material 14 Standard anode or anode 16 Base Anode Material 18 electrolyte 20 Separation Barrier 22 Anode current collector foil 24 Cathode current collector foil 26 Battery housing 28 Schematic flow path 30 Lithium-ion 32 One or more additives 34 Reinforced cathode 36 Metal-coated textiles 38 High aspect ratio conductor 40 Conductive filamentary structures 42 Reinforced Anode 44 Arrow A (discharge direction) Dashed arrow B (discharge direction) Arrow C (charging direction) Dashed arrow D (charging direction)

Claims

1. 1. A battery cathode having improved electrical conductivity for use in a battery, said battery cathode comprising: an active base cathode material comprising lithium iron phosphate; and at least one additive dispersed within the active base cathode material to form a dispersed mixture; The at least one additive is a first additive including a plurality of nickel CVD coated fibers having a diameter of 3 microns to 20 microns, the nickel coating having a thickness of 0.1 microns to 3 microns; and a fiber length of 0.1 mm to 1.0 mm (excluding fiber lengths of 200 μm or less); A battery cathode, wherein said first additive is dispersed in said active base cathode material in a loading range of up to 15% by weight of said active base battery cathode material.

2. 2. The battery cathode of claim 1, wherein each fiber of the plurality of nickel CVD coated fibers is selected from the group of materials consisting of carbon, silica, quartz, silicates, alumina, aluminosilicates, borosilicates, glasses, minerals, carbides, nitrides, borides, polymers, cellulose, inorganic fibers, and organic fibers.

3. 2. The battery cathode of claim 1, further comprising a second additive comprising a conductive nickel filamentary branched structure, the conductive nickel filamentary branched structure being selected from the group consisting of branched nickel powder and nickel nanostrands.

4. 1. A battery cathode having improved electrical conductivity for use in a battery, said battery cathode comprising: An active base cathode material comprising lithium nickel manganese cobalt oxide; and at least one additive dispersed within the base cathode material to form a dispersed mixture; The at least one additive is a plurality of aluminum CVD coated fibers having a diameter of 3 microns to 20 microns, the aluminum coating having a thickness of 0.1 microns to 3 microns; and a fiber length of 0.1 mm to 1.0 mm (excluding fiber lengths of 200 μm or less); A battery cathode, wherein the additive is dispersed in the active base cathode material in a loading range of up to 10% by weight of the active base battery cathode material.

5. 5. The battery cathode of claim 4, wherein each fiber of the plurality of aluminum CVD coated fibers is selected from the group of materials consisting of silica, quartz, silicates, alumina, aluminosilicates, borosilicates, glasses, minerals, nitrides, borides, polymers, cellulose, inorganic fibers, and organic fibers.

Citation Information

Patent Citations

  • Electrode for nonaqueous electrolytic secondary battery and its manufacture

    JP1994302315A

  • Electrical energy device using conductive ceramic fibers

    JP1999512869A

  • Nonaqueous electrolyte secondary battery

    JP2000138062A

  • Coin-form nonaqueous secondary battery

    JP2004335186A

  • Copper-based energy storage device and method

    JP2010514142A